Perumusan Fungsi Green Sistem Osilator Harmonik dengan Menggunakan Metode Integral Lintasan (Path Integral) - Sutisna, Sutisna (Jurnal Fisika FLUX, 2009)
The path integral is a method that often used in the quantum problemscalculation. For example; the calculation of quantum system energy that hascomplex potential form. The method gives more easily than perturbation method.The method is also used to derive Green function, which usually used Fouriertransformation. The Green function has widely application in quantum physics,since it used to compute solution of inhomogen differential equation asSchrodinger equation. In the particle physics, the Green function used aspropagator in Feynmanâs diagram. Considering the importance of Green function,and the powerfull of path integral method, in the paper, the method used toderive the formula of Green function for quantum harmonic oscillator system. Thesystem has widely application to give more information of physical phenomena,for example, the atomic vibration in solid state. The result was also comparedwith Fourier transformation method and both give the same result as hoped.